2020
DOI: 10.22541/au.159827628.89543845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evolutionary trade-off between parasite virulence and dispersal at experimental invasion fronts

Abstract: Changing environments and habitat structure likely affect eco-evolutionary processes involved in the spatial spread of disease. Exploitative parasites are predicted to evolve in highly connected populations or in expanding epidemics. However, many parasites rely on host dispersal to reach new populations, potentially causing conflict between local transmission and global spread. We performed experimental range expansions in interconnected microcosms of the protozoan Paramecium caudatum, allowing natural disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Using 2-patch dispersal arenas, Fellous et al (2011) demonstrated that, on average over five P. caudatum strains, rates of dispersal for infected cultures were lower than those for uninfected controls. A similar trend was found in a recent study by Nørgaard et al (2021).…”
Section: Study Systemsupporting
confidence: 92%
See 2 more Smart Citations
“…Using 2-patch dispersal arenas, Fellous et al (2011) demonstrated that, on average over five P. caudatum strains, rates of dispersal for infected cultures were lower than those for uninfected controls. A similar trend was found in a recent study by Nørgaard et al (2021).…”
Section: Study Systemsupporting
confidence: 92%
“…Previous work in this system had shown that, for a small number of host strains tested, infection reduces dispersal (Fellous et al, 2011;Nørgaard et al, 2021). The first objective of the present study was to test whether this negative effect was general, or whether strains varied in infection state-dependent dispersal.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Swimming is accomplished through the coordinated movement of ciliary bands on the cell surface (Wichterman, 1986). Previous work on P. caudatum indicated a genetic basis of dispersal propensity, and plastic responses are induced by biotic factors, such as parasitism, chemical predator signals, or population density (Fellous et al, 2012;Fronhofer et al, 2018;Zilio et al, 2021). Here, we used 20 Paramecium strains (i.e., clonal mass cultures derived from a single individual) from various geographic origins (Weiler et al, 2020;Zilio et al, 2021) and representing different groups of mitochondrial haplotypes ("COI genotypes" or "genotypes", hereafter; Table S1).…”
Section: Study Organism and Strainsmentioning
confidence: 99%
“…Here, moving a step forward from previous ecological models (Melbourne & Hastings, 2009;Giometto et al, 2014), we employed such a combined approach to assess the predictability of evolutionary outcomes of range expansions in an aquatic model organism, the freshwater protozoan Paramecium caudatum. Following previous studies ) Nørgaard et al (2021, we used interconnected 2-patch systems to establish a range front treatment, where recurrent episodes of dispersal alternated with intermittent periods of population growth. In the contrasting range core treatment, only the non-dispersing individuals were maintained.…”
Section: Introductionmentioning
confidence: 99%